Crossing boundaries : intercontextual dynamics between family and school - Marsico, Giuseppina; Komatsu, Koji; Iannaccone, Antonio (Emerald Publishing Limited : Information Age Publishing, Inc., 2013)
This book brings in the focus on the borders between different contexts that need to be crossed, in the process of education.Despite the considerable efforts of various groups of researchers all over the World, it does not seem that traditional educational psychology has succeeded in illuminating the complex issues involved in the schoolfamily relationship. From a methodological perspective, there is no satisfactory explanation of the connection between representations and actual practice in educational contexts.Crossing Boundaries is an invitation to cultural psychology of educational processes to overcome the limits of existing educational psychology.Eemphasizing social locomotion and the dynamic processes, the book try to capture the ambiguous richness of the transit from one context to another, of the symbolic perspective that accompanies the dialogue between family and school, of practices regulating the interstitial space between these different social systems.How family and school fill, occupy, circulate, avoid or strategically use this space in between? What discourses and practices saturate this Border Zone and/or cross from one side to the other?Crossing Boundaries gathers contributions with the clear aim of documenting and analysing what happens at points of contact between family culture and scholastic/educational culture from the perspective of everyday life.This book is in itself an attempt to cross the border between the "theorizing on the borders" (and how "the outside world" and "the others" are perceived from a certain point of view) and "the practices" that characterize the school-home interaction.
Keywords: Home and school -- Cross-cultural studies.; Education -- Parent participation -- Cross-cultural studies.; Multicultural education -- Cross-cultural studies.; Psychology -- Social Psychology.; Educational psychology.; Social, group or collective psychology.; elektronické knihy; electronic books